Virtual Wheelchair Accessibility Evaluation Tool for Virtual Environments: Design and Preliminary Tests - Monteiro, Erico Patricio; Campos, Alexandre; Gitirana, Marcelo; Oviedo, Rafael (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
The growing demand for inclusivity towards accessibility in various social settings leads to stricter global standards, which emphasize the importance of having an assessment tool to gauge the virtual environment experience of wheelchair users. This proposal introduces a virtual reality manual wheelchair simulator able to capture trajectory and time metrics. The objective is to provide designers, architects, and wheelchair users with valuable data for redesign or comparison among virtual environments. The preliminary results of this study indicate promising feasibility in terms of user displacement, although certain aspects of the virtual interface, particularly those related to physics and dynamics calculations, still require improvement. Future work should address those aspects, focus on in-editor modular integration, track check-point system and a questionnaire system.